Concussion in the emergency department; unconsciously incompetent?. Issue 11 (25th May 2017) - Phillips, Thom; Guy, Katie; Martin, Rhodri; Tomkinson, Alicia; Phillips, Dan; Sloane, Nicole
Abstract : Objective: Sports related concussion is an increasingly common occurrence. Outside professional sport it is typically managed within Emergency Departments. The objective was to assess the level of knowledge and understanding of UK emergency medicine doctors of concussion; it's recognition, diagnosis and management. Design: Cross-sectional observational study using self-report questionnaires. Setting: Questionnaires were distributed at regional EM conferences between October 2015 and January 2016. 15 secondary and 5 tertiary care centres were represented. Participants: 156 questionnaires were completed. Illegible answers, defaced or incorrectly completed questionnaires were discarded. 134 were included in the analysis. Training levels represented were: Consultant (10%), Specialist Registrar (12%), Staff Grade (5%), Core Trainee (34%), Foundation Trainee (20%), Emergency Nurse Practitioners (1.5%), Medical Students (16%). Interventions (or Assessment of Risk Factors): The questionnaire asked respondents to correctly identify signs and symptoms of concussion according to the Zurich consensus statement. It asked whether there were differences in the management of adult and paediatric concussion together with questions regarding RTP guidelines and use of potentially protective equipment. Main results: Consultants obtained the highest signs and symptoms score (6.2). The least correct were Specialist Registrars (2.0). Diagnostic accuracy did not differ between secondary and tertiary centres (p=0.67). 80% of participants incorrectly identified headguards as being protective against concussion. 35.4% of respondents acknowledged a difference between adult and paediatric concussion. Conclusions: This small yet representative sample highlights a lack of knowledge in concussion in health professionals working in EDs in the UK. Efforts to improve the knowledge and understanding of concussion are required given the increasing awareness of the impact and occurrence of sports concussion. Competing interests: None.